Evaluation of delphinidin as a storage medium for avulsed teeth - Ok Hyung Nam; Sang Tae Ro; Hyeon-Woo Lee; Jaeki Jeong; Yong Kwon Chae; Ko Eun Lee; Sung Chul Choi; Sang Wook Kang (BMC, 2023)
Abstract Background Delphinidin (DP), an anthocyanidin found in blueberries, has antioxidant and anti-inflammatory effects. This study aimed to investigate the efficacy of DP as a storage medium for avulsed teeth. Methods Human periodontal ligament cells were cultured and exposed to DP solution (10, 50, and 100 μM), Dulbecco's modified Eagle's medium, Hank's balanced salt solution and tap water. Cell counting kit-8 assays were performed after 0.5, 1, 6, and 24 h to measure the cell viability. Nitric oxide assays and gelatin zymography were performed to evaluate the anti-inflammatory effects of DP. Reverse transcription-polymerase chain reaction was used to determine the expression levels of inflammatory cytokines. Results The viability of periodontal ligament cells was greatest at 100 μM DP. At 1 h, 100 μM DP decreased nitric oxide synthesis (p < .0167). Matrix metallopeptidase-9 activity was inhibited by DP in a dose-dependent manner (p < .0167). Moreover, treatment with 100 μM DP decreased the expression levels of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-8 in periodontal ligament cells (p < .0167). Conclusions Within the limits of this study, DP preserved the viability and suppressed the inflammatory response of periodontal ligament cells. These findings suggest that DP could be promising for preservation of avulsed teeth.